[(11)C]Cyanation of Arylboronic Acids in Aqueous Solution - Ma, Longle (Chem Commun (Camb), 2017)
A copper-mediated (11)C-cyanation method employing arylboronic acids and [(11)C]HCN has been developed. This method was applied to the radiochemical synthesis of a wide range of aromatic (11)C-nitriles in aqueous solutions. The use of readily accessible arylboronic acids as precursors makes this method complementary to the well-established (11)C-cyanation methods that utilize aryl halide precursors.